META ANALYSIS: THE EFFECT OF COOPERATIVE LEARNING MODELS ON STUDENTS' CRITICAL THINKING ABILITIES - Nur, Fitriani; Asdar, Fajriani; Majid, Ahmad Farham (IAIN Ambon, 2024)
Critical thinking skills are one of the important competencies that students must have in facing the challenges of the 21st century. These skills include the ability to effectively analyze, evaluate and synthesize information, which is crucial in making informed decisions and solving complex problems. Cooperative learning models have great potential in improving these skills by engaging students in group work that encourages interaction, discussion and sharing of ideas. There are many studies related to the application of cooperative learning models in improving students' critical thinking skills so that meta-analysis research is conducted to combine the results of these studies into one conclusion. This research was conducted to determine the effect of cooperative learning models on students' critical thinking skills. This research used a quantitative approach with the type of meta-analysis research. Data collection was carried out by searching for research reports in accordance with the topics studied on internet network sites. The sampling technique used purposive sampling technique. The instrument used was a data collection sheet. Data analysis was carried out using descriptive statistics and inferential statistics. Based on the research conducted, it is concluded that the cooperative learning model affects the critical thinking skills of students. Thus, cooperative learning models are effective compared to conventional models in improving students' critical thinking skills. Keywords: Cooperative Learning; Critical thinking; Meta Analysis